PENDIDIKAN KESEHATAN PADA IBU NIFAS MEMPERLANCAR PRODUKSI ASI - Ernawati Ernawati; Siti Nurjanah; Desi Widyastutik; Erinda Nur P (PENA ABDIMAS : Jurnal Pengabdian Masyarakat, 2022)
Malnutrition in infants is caused by the increasing nutritional needs of infants. Breast engorgement is influenced by the frequency of the mother to breastfeed, the duration of breastfeeding, the initiation of early breastfeeding, static breastfeeding, the initial experience of breastfeeding. Breast engorgement is often experienced by the mother due to sore or sore nipples. Approximately 57% of breastfeeding mothers reported having experienced blisters on their nipples (Soetjiningsih, 2012). To prevent breast engorgement due to breast milk damages and accelerate the lactation process, breast care can be carried out. In addition, there are non-pharmacological drugs, namely the provision of purslane leaves for the smooth production of breast milk. With the provision of purslane leaves, it is a suitable means of partnering problems. In the end, it is hoped that it can help improve the understanding of postpartum mothers in overcoming problems in overcoming smooth production to prevent breast engorgement. Keyword : purslane leaves, breast care, smooth milk production.